If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3.1x+7-7.4x=1.5x-6(x-3/2
We move all terms to the left:
3.1x+7-7.4x-(1.5x-6(x-3/2)=0
We add all the numbers together, and all the variables
3.1x-7.4x-(1.5x-6(+x-3/2)+7=0
We add all the numbers together, and all the variables
-4.3x-(1.5x-6(+x-3/2)+7=0
We multiply all the terms by the denominator
-(4.3x)*2)+7-(1.5x-6(+x-3=0
We add all the numbers together, and all the variables
-(+4.3x)*2)+7-(1.5x-6(+x-3=0
| .25x=-10 | | 5k^2=k^2-3k | | 2-3x=2+x | | 6=3(x-3) | | -6(9k-4)=23 | | x+2/3=2x+6/8 | | 7(0)-5y=12 | | 3k+4-5k=22k+12 | | 150m-75m+43,425=45450-150m | | x-3(-6x+5)=-130 | | 6(g−80)=84 | | 5t^2-10t=0 | | (9x+4)/(3x-3)=0 | | 3m−6=12 | | 2+2(c-1)=22 | | 5x-3(-6x+5)=-13 | | 9f-3+8=30 | | 15-3x=15+(-3x) | | 8-y=y^2 | | 18=2/5*f | | 6=1/2(9x+10) | | 2(y+2)-2=3(y-1)-2y | | 4h+7=11 | | 5v-8v=-30 | | 136=-8(1-3n) | | 8÷11(n-10)=64 | | 2x=3x^2-4 | | 2x^2=3x^2-4 | | 3+3y=6y | | 2a-7/8=-1/4 | | 3/5s=1/4 | | 68-x=22 |